2004
DOI: 10.1111/j.1348-0421.2004.tb03519.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Switching and β‐N‐Acetylhexosaminidase Activity of the Pathogenic Yeast Trichosporon asahii

Abstract: The genus Trichosporon includes approximately 30 species, of which at least six are associated with infection (trichosporonosis): T. asahii, T. mucoides, T. asteroides, T. cutaneum, T. inkin, and T. ovoides (7, 9). The first two species are responsible for deep-seated infection, and the last four are involved in superficial infection, including white piedra. More than 90% of deep-seated trichosporonosis is caused by T. asahii. Most patients with deep-seated trichosporonosis have an underlying hematological ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
(29 reference statements)
2
22
0
3
Order By: Relevance
“…Those authors observed that strains of the three major types usually developed two to five colony types and switched at a frequency of 10 2 to 10 4 when grown at 37°C, similar to that observed with Candida albicans and Cryptococcus neoformans (4,59,87). Most of the colonies switched irreversibly to the smooth type, which had the greatest beta-N-acetylhexosaminidase enzymatic activity compared with the parent type in all strains (84).…”
Section: Enzymessupporting
confidence: 59%
See 1 more Smart Citation
“…Those authors observed that strains of the three major types usually developed two to five colony types and switched at a frequency of 10 2 to 10 4 when grown at 37°C, similar to that observed with Candida albicans and Cryptococcus neoformans (4,59,87). Most of the colonies switched irreversibly to the smooth type, which had the greatest beta-N-acetylhexosaminidase enzymatic activity compared with the parent type in all strains (84).…”
Section: Enzymessupporting
confidence: 59%
“…No other clinically relevant Trichosporon spp. have been shown to produce this enzyme (84). The same study also reported 4 different morphological types of colonies grown on Sabouraud dextrose agar (SDA), i.e., white farinose (69%), white pustular (18%), yellowish white (10%), and white cerebriform (3%).…”
Section: Enzymesmentioning
confidence: 78%
“…PS has been demonstrated and described for pathogenic yeasts, including C. albicans (3,12,15,16,19,20,21,23,25,26), Candida glabrata (2, 10, 22), T. asahii (9), and C. neoformans (7). As a manifestation of apparent developmental programming, PS confers phenotypic variability and environmental adaptation that facilitates the survival and/or pathogenic success of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic switching is an attractive explanation for such phenotypic variations in C. lusitaniae, since switching has been documented for other pathogenic yeasts, including Candida albicans (3,12,15,16,19,20,21,23,25,26), Candida glabrata (2,10,22), Trichosporon asahii (9), and Cryptococcus neoformans (7). This mechanism permits an organism to adapt to environmental changes through selective gene expression, including changes in the fungal response to antifungal agents.…”
mentioning
confidence: 99%
“…В нескольких опубликованных случаях продемонстри-рована хорошая эффективность азолов против рода Trichosporon, однако есть сообщения и о мультиле-карственной устойчивости к амфотерицину B, флюци-тозину, флюконазолу, итраконазолу [14]. В недавних исследованиях новые триазолы -вориконазол, поза-коназол и равуконазол -показали хорошую эффек-тивность in vitro против Trichosporon [15]. С другой стороны, проведенные исследования свидетельству-ют о том, что эхинокандины -каспофунгин, анидула-фунгин -вряд ли будут эффективны против разно-видностей Trichosporon [16].…”
Section: рисунокunclassified